Solve. -7-7(x -5)-8x +13 = -2(x + 5) - 9x
Answers
Answered by
1
Answer:
x= 51/4
Step-by-step explanation:
see attached pic.like if its helpful.
Attachments:
![](https://hi-static.z-dn.net/files/dc0/6b0ce5883369d077fa7a2ad05dbdf2f1.jpg)
Answered by
1
Answer:
-4 is not equal to 3
Step-by-step explanation:
-7-7(x + 5)-8x + 13 = -2(x+5) - 9x
= -14 (x+5)-8x+13 = -2(x+5) - 9x
x= 5 + (-14)-8x+13 = x= -2 +5
= 5-14 -8x+13 = 3-9x
x = -9 -8x+13 = 3 -9x
-8x = 13 - 9 = 3 = 9x
-8x = 4 = x = 9/3
x = 4 - 8 x = 3
= -4
So -4 is not equall to 3
Similar questions